Glioma stem cell (GSC)‐derived autoschizis‐like products confer GSC niche properties involving M1‐like tumor‐associated macrophages. (11th May 2020) - Tabu, Kouichi; Liu, Wenyu; Kosaku, Akina; Terashima, Kazuo; Murota, Yoshitaka; Aimaitijiang, Alapati; Nobuhisa, Ikuo; Hide, Takuichiro; Taga, Tetsuya
Abstract: Spontaneous necrosis is a defining feature of glioblastomas (GBMs), the most malignant glioma. Despite its strong correlations with poor prognosis, it remains unclear whether necrosis could be a possible cause or mere consequence of glioma progression. Here we isolated a particular fraction of necrotic products spontaneously arising from glioma cells, morphologically and biochemically defined as autoschizis‐like products (ALPs). When administered to granulocyte macrophage colony‐stimulating factor (GM‐CSF)‐primed bone marrow‐derived macrophage/dendritic cells (Mφ/DCs), ALPs were found to be specifically engulfed by Mφs expressing a tumor‐associated macrophage (TAM) marker CD204. ALPs from glioma stem cells (GSCs) had higher activity for the TAM development than those from non‐GSCs. Of note, expression of the Il12b gene encoding a common subunit of IL‐12/23 was upregulated in ALPs‐educated Mφs. Furthermore, IL‐12 protein evidently enhanced the sphere‐forming activity of GBM patient‐derived cells, although interestingly IL‐12 is generally recognized as an antitumoral M1‐Mφ marker. Finally, in silico analysis of The Cancer Genome Atlas (TCGA) transcriptome data of primary and recurrent GBMs revealed that higher expression of these IL‐12 family genes was well correlated with more infiltration of M1‐type TAMs and closely associated with poorer prognosis in recurrent GBMs. Our results highlight a role of necrosis in GSC‐driven self‐beneficial niche construction and glioma progression, providing important clues for developing new therapeutic strategies against gliomas. Abstract : Strategic necrosis of glioma stem cells (GSCs) to develop GSC‐friendly M1‐type tumor‐associated macrophage.